Inclusive learning through immersive virtual reality and semantic embodied conversational agent: a case study in children with autism - Alvarado, Yoselie (2023)
Sustainable Development Goal 4 from the United Nations 2030 Agenda, focus on ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all. Inclusive education is a key component of sustainable development goal 4, and assistive technology is a critical factor in achieving it. In this context, this paper introduces the development of an immersive virtual reality system with conversational skills for inclusive learning processes. The idea of this work is to provide an assistive technology to motivate, educate, and train students with disabilities in a more inclusive way. In order to improve the user experience, the system was developed to work in a CAVE-like immersive environment using Natural Language Processing through a Semantic Embodied Conversational Agent. This work highlights that assistive technology can promote educational, psychological, and social benefits for students with disabilities. The use of assistive technology can enable academic engagement and social participation and be transformative from a psychological perspective. A case study was conducted on children with autism, which showed encouraging results of the system as an assistive technology for teaching and learning.